2022
DOI: 10.1002/jcsm.13070
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass, muscle strength and mortality in kidney transplant recipients: results of the TransplantLines Biobank and Cohort Study

Abstract: Background Survival of kidney transplant recipients (KTR) is low compared with the general population. Low muscle mass and muscle strength may contribute to lower survival, but practical measures of muscle status suitable for routine care have not been evaluated for their association with long‐term survival and their relation with each other in a large cohort of KTR. Methods Data of outpatient KTR ≥ 1 year post‐transplantation, included in the TransplantLines Biobank and Cohort Study (http://ClinicalTrials.gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Similarly, our prior meta-analysis observed a consistent inverse relationship between higher upper extremity muscle strength and all-cause mortality [ 8 ]. A recent cohort study evaluating the association between handgrip strength index and mortality in kidney transplant recipients yielded similar results [ 40 ]. Despite the availability of handgrip strength reference values for different populations, there are few reports on the optimal handgrip strength for preventing all-cause mortality in CKD.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, our prior meta-analysis observed a consistent inverse relationship between higher upper extremity muscle strength and all-cause mortality [ 8 ]. A recent cohort study evaluating the association between handgrip strength index and mortality in kidney transplant recipients yielded similar results [ 40 ]. Despite the availability of handgrip strength reference values for different populations, there are few reports on the optimal handgrip strength for preventing all-cause mortality in CKD.…”
Section: Discussionmentioning
confidence: 66%
“…In model 3, we additionally adjusted for plasma haemoglobin (Hb). In sensitivity analyses, we substituted CER for length‐indexed CER 17 and length^2‐indexed CER, 18 given that muscle mass depends on body size. Furthermore, we repeated the analyses after exclusion of the 5% most extreme ferritin or TSAT values by calculating absolute differences from the median.…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies have reported beneficial effects of dialysis on skeletal muscle, such as the reduction of skeletal muscle fibrosis, the restoration of satellite cell populations, and an overall increase in muscle strength and endurance [135]. Clearly, transplantation is the treatment of choice for ESRD patients, as it improves survival and quality of life, including increases in physical performance and muscle strength [434][435][436]. Surprisingly, to date, only a few studies have analyzed skeletal muscle tissue in transplanted CKD patients to determine changes on histological, cellular, and molecular levels.…”
Section: The Effects Of Dialysis and Kidney Transplantation On Ckd-as...mentioning
confidence: 99%